2022
DOI: 10.47102/annals-acadmedsg.2021329
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to breast cancer screening in Singapore: A literature review

Abstract: Introduction: Breast cancer is a leading cause of cancer death among women, and its age-standardised incidence rate is one of the highest in Asia. We aimed to review studies on barriers to breast cancer screening to inform future policies in Singapore. Method: This was a literature review of both quantitative and qualitative studies published between 2012 and 2020 using PubMed, Google Scholar and Cochrane databases, which analysed the perceptions and behaviours of women towards breast cancer screening in Sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, even with a nation-wide screening programme, over 60% of Singaporean females between the ages of 50 and 69 years do not attend regular mammography at recommended intervals [ 7 , 8 ]. Studies over the past 25 years showed little change in women’s barriers and motivations to attend mammography screening, with recurring main themes such as fear, cost, inconvenience, and a perceived lack of risk [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, even with a nation-wide screening programme, over 60% of Singaporean females between the ages of 50 and 69 years do not attend regular mammography at recommended intervals [ 7 , 8 ]. Studies over the past 25 years showed little change in women’s barriers and motivations to attend mammography screening, with recurring main themes such as fear, cost, inconvenience, and a perceived lack of risk [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In rural areas, poor health literacy, belief in alternative therapy, cancer fatalism, and lack of autonomous decision-making have been reported in many Asian countries. 34 Even in HICs like Singapore, where multiple channels for screening are available, screening uptake remains low indicating psychosocial barriers in these settings, 35 fear of the financial burden associated with the costs of breast cancer treatment has been reported, as the government adopts a co-payment mode for health services. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…Through a thematic analysis based on the Health Belief Model, significant themes associated with low breast cancer screening uptake were identified. The themes are: high perceived barriers versus benefits, including fear of the breast cancer screening procedure and its possible out-comes, personal challenges that impede screening attendance and paying for screening and treatment, and low perceived susceptibility to breast cancer ( 16 ). Low- and middle-income countries (LMICs) grapple with restricted financial resources, apportioning relatively smaller segments to healthcare budgets ( 17 ).…”
Section: Discussionmentioning
confidence: 99%